Designing a Media Literacy Curriculum Model for Teacher Training Centers - Nabipoor , Afsaneh; Rahmani , Jahanbakhsh; Taghipour , Faezeh (Iranian Journal of Educational Sociology, 2022)
Purpose: The present study was conducted to design a model of media literacy curriculum in teacher training centers. Methodology: This research was applied in terms of purpose and qualitative in terms of research method and data type. Experts in the field of media literacy and education, including university professors, were considered as the research community. By conducting a snowball method with 20 interviews, the collected information reached saturation point. The data collection tool was a review of relevant national and international research as well as a semi-structured exploratory interview. Finally, after collecting information from the interview sections and reviewing the sources, at this stage, the data foundation and coding methods were used to classify the data. In order to check the internal validity of the findings, in addition to selecting and confirming the data by studying theoretical foundations, research background, sources, and interviews with focal individuals, the opinions and guidelines of a group of experts were also taken into account. The final was done. In order to confirm the accuracy of the data, the study method was used by the research members to validate the study. Findings: The findings of the study indicated that the appropriate model of media literacy curriculum for teacher training centers, consisting of dimensions such as public media literacy, specialized media literacy, media understanding, media management, media construction and Moral literacy was media. Conclusion: Media literacy is a technique that strengthens the discriminating power by creating dynamism against media messages.